Międzynarodowe i lokalne próby aktywizacji byłych żołnierzy Pierwszej Polskiej Dywizji Pancernej w Belgii w latach 1947–1970 - Venken, Machteld (Pamięć i Sprawiedliwość, 2011)
This article offers an insight into the organisational landscape of former First Polish Armoured Division soldiers during their first phase of settlement in Belgium, between 1947 and 1970. It analyses how formal immigrant organisations gathering former division soldiers in Belgium arouse under the influence of mobilising agencies in Great Britain, the Polish People’s Republic and Belgium. These agencies were at some point pre-occupied with the outbreak of a possible World War III, while at other moments focusing on the way World War II was remembered. All articulating their own, specific, war memories, they clashed over who and what should be remembered, and had an interest in having the former division soldiers remembering World War II in line with the way they did. This created a powerstruggle with various mechanisms including or excluding former division soldiers in Belgium, a struggle which over time led to changes in mobilisation and denial policies towards them. I question how mobilising agencies promoted their case, gained power and reshuffled relations towards former division soldiers in Belgium by means of immigrant organizations.